Macropinocytosis activated by oncogenic Dbl enables specific targeted delivery of Tat/pDNA nano-complexes into ovarian cancer cells - Niu X (Dove Medical Press, 2018)
Xiuran Niu,1,* Zhihui Gao,1,* Shanshan Qi,1 Linjia Su,1 Nan Yang,1 Xiuli Luan,1 Jia Li,1 Qing Zhang,2 Yingli An,3 Sihe Zhang1 1Department of Cell Biology, School of Medicine, Nankai University, Tianjin, People’s Republic of China; 2Department of Clinical Laboratory, Cancer Hospital of Tianjin Medical University, Tianjin, People’s Republic of China; 3State Key Laboratory of Medicinal Chemical Biology and Institute of Polymer Chemistry, Nankai University, Tianjin, People’s Republic of China *These authors contributed equally to this work Background: Successful implementation of gene therapy heavily relies on efficiently delivering genetic materials and specific targeting into cells. Oncogene-driven endocytosis stimulates nutrient uptake and also develops an endocytosis-mediated defense against therapeutic agents. Cell-penetrating peptides, typically HIV-Tat, are well known for efficient delivery of nucleic acid drugs but lack targeting specificity. Various passive targeting strategies were pursued to enhance the tumor targeting efficiency; however, they are still limited by complicated cellular endocytosis routes and the heterogeneity of cancer types. Methods: Tat/pDNA complexes were noncovalently compacted and their physiochemical properties were determined. The siRNA pool and pLV-RNAi-GFP lentivirus were used to knock down dbl oncogene (originally isolated from diffuse B-cell lymphoma) expression, and its overexpression was performed by plasmid transient transfection. The cellular uptake of fluorescent ligands was quantified by confocal imaging and flow cytometry analysis. The transgene efficiency was determined by the Luciferase expression assay. Rho GTPase activation was checked by the GST-Rho GTPase-binding domain pull-down assay. Results: pGL3 plasmid DNA was noncovalently compacted with the Tat peptide into nano-size complexes at high N/P ratios. Macropinocytosis, a clathrin- and caveolin-independent endocytosis process, was shown to contribute to the uptake of middle-sized (~600 nm) Tat/pGL3 complexes. Cell-type-specific variation in macropinocytosis was essentially controlled by the action of the Dbl oncogene. Onco-Dbl presentation constantly induced a high level of macropinocytosis activity in ovarian cancer cells. Onco-Dbl overexpression hyperstimulated macropinocytosis enhancement in cells mainly through actin cytoskeleton reorganization mediated by the PH domain and Rac1 activation. The Dbl-driven Rho GTPase signaling collectively determined the cell-type-specific macropinocytosis phenotype. Conclusion: Such an aspect can be exploited to selectively confer targeted delivery of Tat/pDNA nano-complexes into ovarian cancer cells. Our work provides a novel alternative for targeted delivery of cell-penetrating peptide-based nucleic acid drugs into certain tumor types if specific endocytosis pathways are used. Keywords: onco-Dbl, macropinocytosis, Rac1, Tat/pDNA complex, targeting delivery